Determining the gap for UW-Stout student supervisor training - Lor, Mai Joua (University of Wisconsin--Stout, 2018)
The purpose of this study was to determine whether or not the addition of online training as a delivery method would be effective in assuring that newly appointed UW-Stout student employee supervisors can receive EDGE training in a timely manner. Since it is not possible to determine in advance who a new supervisor would be, or when they would become a supervisor, and what their delivery preferences are. Due to the large number of supervisors and the crucial roles a supervisor serves in the hiring and orienting of the student employees, the UW-Stout's HR department believes that it is essential to offer training sessions for all supervisor in this role. An online survey of 12 questions was used to collect data and analyze results. The survey was administered 286 active supervisors of student employees with the response rate of 37%. Data analysis and results indicated that the participants of this study agreed with the UW-Stout Human Resources department to implement an online EDGE training session in additional to the face-to-face training during the beginning of the academic year. Furthermore, the results showed that supervisors preferred a blended (both online and in person training) method of learning.
Keywords: Supervisors; Training needs; Students; Employees